A Actual Regulação do Crédito ao Consumo - Ramirez, Paulo Nuno Horta Correia (Journal of Business and Legal Sciences / Revista de Ciências Empresariais e Jurídicas, 2011)
"All of us are consumers" John Kennedy said impressively on 15 March 1962. And we would say that many of us are "credit consumers". It is in this context that the recent approval, in our legal disposition, of a new regulating norm of the consumption credit, assumes special relevance. On the other hand, one should emphasize the constitutional command which takes into account the consumers protection. Actually, according to article 60 of the Portuguese Republic Constitution, "the consumers have a right to the quality of goods and services consumed, to training and information, to the protection of health, of safety and of economic interests, as well as to the repair of damages". Therefore, it is important to know with rigour the norms that nowadays rule the access and the regulation of consumption credit contracts, in a context of communitarian harmonization of this legal-economic institution. It will be convenient, above all, to understand how the do-cument, which nowadays rules the present issue, protects, in a more stressing way, the part which is economically considered the weakest.